Effect of Work Stress and Work Environment on Employee Performance at PT. Alamjaya Wirasentosa Tanjung Morawa in 2021 - Sisca Amini Cahya Agitsna; Marliyah Marliyah (Budapest International Research and Critics University, 2022)
In general, employee performance is very important for the running of a company. Employee performance is one form of success of a company or failure of a company. Of course, to make the company's success a form of employee performance, companies need to pay attention to work stress and the employee's work environment. Where work stress and work environment can affect employee performance. This study aims to see how much influence work stress and work environment have on employee performance. The method used is a quantitative method. The object or target of this research is the employees of PT. Alamjaya Wirasentosa Tanjung Morawa. The results showed that based on the results of the T-test, the work stress variable had a significant level of 0.004 < 0.05 and the work environment variable had a significant level of 0.000 < 0.05. In the results of the F-test research, the significant value of the variable is 0.000 < 0.05. Seeing from these results, it is stated that all independent variables namely work stress and work environment have a simultaneous and significant influence on the dependent variable, namely employee performance at PT. Alamjaya Wirasentosa Tanjung Morawa.